2018
DOI: 10.11591/ijece.v8i1.pp26-33
|View full text |Cite
|
Sign up to set email alerts
|

A Coalition-Formation Game Model for Energy-Efficient Routing in Mobile Ad-hoc Network

Abstract: One of the most routing problems in Mobile Ad-hoc Network is the node’s selfishness. Nodes are generally selfish and try to maximize their own benefit; hence these nodes refuse to forward packet on behalf of others to preserve their limited energy resources. This selfishness may lead to a low efficiency of routing. Therefore, it is important to study mechanisms which can be used encourage cooperation among nodes, to maintain the network efficiency. In this paper, we propose a cooperative game theoretic model t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Also, very few studies are found to analyze the problem of packetforwarding between nodes with an efficient and evolving game approach. Studies have claimed that the game modelling approach can encourage cooperative data forwarding and can also increase the throughput performance in MANET routing [13], [14], [36]. • Despite having various advantages, limited studies have cited game-based decision modelling to assess individual node actions in MANET dynamic routing [28], [29], [37].…”
Section: Problem Findings and Gap Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Also, very few studies are found to analyze the problem of packetforwarding between nodes with an efficient and evolving game approach. Studies have claimed that the game modelling approach can encourage cooperative data forwarding and can also increase the throughput performance in MANET routing [13], [14], [36]. • Despite having various advantages, limited studies have cited game-based decision modelling to assess individual node actions in MANET dynamic routing [28], [29], [37].…”
Section: Problem Findings and Gap Analysismentioning
confidence: 99%
“…• The analysis of the existing literature also shows that very few approaches jointly address the energy and network performance issues. This is because their intelligent game models might have provided convergence towards better throughput solution but do not ensure effective energy and delay performance in the real-time context from the application requirement viewpoint [23]- [27], [36], [37], [40]. • There are algorithms for identifying the self-centred nodes during the packet forwarding activities but very lesser studies concerned about designing the algorithms with minimal computational requirements such as memory, processing time, etc.…”
Section: Problem Findings and Gap Analysismentioning
confidence: 99%
“…Riahi and Riahi [41] have discussed about game theory for resource distribution in a huge allocated techniques. Sahnoun et al [42] presented a model called A Coalition-Formation Game model for power efficient routing in MANET. Ahuja and Bedi [43] have developed a technique which is semi blind digital watermaking technique using for video developing MPEG-2 standard.…”
Section: Introductionmentioning
confidence: 99%
“…OLSR contains a kind of control traffic messages (TC messages), periodically exchanged by nodes to build links map with their neighbors [16]. "Hello" messages are typesof broadcasted messages to discover symmetric linkswith their one-hop neighbors.…”
mentioning
confidence: 99%